The use of closed incision negative pressure therapy for incision and surrounding soft tissue management: Expert panel consensus recommendations. Issue 3 (12th August 2021) - Silverman, Ronald P.; Apostolides, John; Chatterjee, Abhishek; Dardano, Anthony N.; Fearmonti, Regina M.; Gabriel, Allen; Grant, Robert T.; Johnson, Owen N.; Koneru, Suresh; Kuang, Anna A.; Moreira, Andrea A.; Sigalove, Steven R.
Abstract: As the use of closed incision negative pressure therapy (ciNPT) becomes more widespread, dressing designs have evolved to address implementation challenges and meet surgeon demand. While traditional application of ciNPT was limited to the immediate suture line, a novel dressing that covers the incision and additional surrounding tissues has become available. To expand upon previous ciNPT recommendations and provide guidance on this new dressing, an expert panel of plastic surgeons convened to review the current literature, identify challenges to the implementation and sustainability of ciNPT, and use a modified Delphi technique to form a consensus on the appropriate use of ciNPT with full‐coverage dressings. After three rounds of collecting expert opinion via the Delphi method, consensus was reached if 80% of the panel agreed upon a statement. This manuscript establishes 10 consensus statements regarding when ciNPT with full‐coverage foam dressings should be considered or recommended in the presence of patient or incision risk factors, effective therapeutic settings and duration, precautions for use, and tools and techniques to support application. The panel also discussed areas of interest for future study of ciNPT with full‐coverage dressings. High‐quality, controlled studies are needed to expand the understanding of the benefits of ciNPT over the incision and surrounding tissues.